Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1111/j.1600-0463.2008.00008.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of equine herpesvirus‐1 infection in the mouse model

Abstract: Equine herpesvirus-1 (EHV-1) is a major equine pathogen causing respiratory diseases, abortions and severe neurological disorders. The basis of neurological disturbances is, as in other organs, infection of endothelial cells, followed by vasculitis, thrombosis and ischaemic damage of the parenchyma. Here, a murine model was used to explore the mechanism of entry to, and spread within the brain, the cell affinity of the agent and the modulating role of the immune defence, which are all factors governing the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
0
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 49 publications
(76 reference statements)
6
31
0
7
Order By: Relevance
“…No viral DNA was detected at 7 to 11days PI. Mouse tissues collected from control animals didn't show any DNA PCR product, and they were negative for EHV-1 (Table, 2 In mice inoculated with male donkey samples, the virus followed the same sequence of antigen fate reported by many authors (14)(15)(16). This finding might indicate that the infection of such donkey has recently occurred or might be related to reactivation of the virus from past infection.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…No viral DNA was detected at 7 to 11days PI. Mouse tissues collected from control animals didn't show any DNA PCR product, and they were negative for EHV-1 (Table, 2 In mice inoculated with male donkey samples, the virus followed the same sequence of antigen fate reported by many authors (14)(15)(16). This finding might indicate that the infection of such donkey has recently occurred or might be related to reactivation of the virus from past infection.…”
Section: Resultssupporting
confidence: 55%
“…Thus these cells become important reservoirs for persistent viral infection (12 and 13). Mice were used as a potential animal model in experimental infections for this virus by many workers (14)(15)(16). Experimentally infected mice with EHV-1 produced clinical signs, like respiratory distress and weight loss (16 and 17).…”
Section: Introductionmentioning
confidence: 99%
“…Gosztonyi et al [9] reported that EHV-1 behaved neurotropic in CNS of mice in contrasted with in horse. In the present study, vasculitis with perivascular mononuclear cuffing found in the brain of mice infected with 89c1, 90c18, 97c11, 98c12, 01c1, or Ab4p was consistent with the lesion found in the brain of natural EHV-1 infected horse from the outbreak of neurological disease [17].…”
Section: Discussionmentioning
confidence: 99%
“…Mice genetically susceptible to EHV-1 infection (Awan et al 1990, Gosztonyi et al 2009) Balb/c (H-2d) were used to establish primary culture of murine neurons. Balb/c mice aged 6-8 weeks were purchased from the Centre for Experimental Medicine (Warsaw) and were treated in accordance with the guidelines regarding the use and care of laboratory animals.…”
Section: Nerve Cell Culturesmentioning
confidence: 99%
“…Therefore, pathogenesis of EHV-1 infection and other phenomena associated with productive and latent infections mostly studied in animals models. An excellent model is the BALB/c mouse, because it has been demonstrated that EHV-1 infection in this mouse strains is similar to that of the natural host (Awan et al 1990, Walker et al 1999, Gosztonyi et al 2009). Accordingly, in the acute form, viremia developes, the virus replicates in the respiratory system and virus tropism to fetuses can be observed in pregnant females.…”
mentioning
confidence: 99%